Exploring barriers to diversified dietary feeding habits among adolescents in the agrarian community, North West Ethiopia - Agedew, Eskezyiaw; Abebe, Zeweter; Ayelign, Abebe (Frontiers in Nutrition, 2022)
Introduction: Adolescence is a critical and neglected age group of population in any form of nutritional intervention. A comprehensive study that assesses barriers that influence their diversified feeding habit is not well investigated in qualitative approaches. Therefore, this study was conducted to fill this gap by providing evidence on exploring barriers for diversified feeding habits of adolescents in Agrarian community, North West Ethiopia. Objective: The aim of the study was to explore barriers for diversified feeding habits of adolescents in Agrarian community, North West Ethiopia. Methods: A phenomenological qualitative study design was conducted. In-depth interviews, and household food environmental observation were utilized for data collection. The audio-recorded qualitative data was transcribed word by word to English. Finally, the translated data was exported to ATLAS ti version 7.1 software for thematic analysis based on inductive content analysis. All coded quotations, including memos written throughout the coding process, were then analysed to identify themes inductively. Results: Dietary habit of adolescents in the study area was predominantly plant-based cereals with low protein, vitamins and mineral content of food items. Adolescents have limited consumption of fruits, vegetables and animal source foods. As a result these feeding habit, adolescent’s had suboptimal intake of micro- nutrients and proteins that are crucial for fast stage of growth. Dietary habits of adolescents were influenced by multiple and interconnected influenc which were identified as individual-level barriers, family level influence, dietary tradition of community, agricultural practice (poor agroforestry practice of the community, and poor agricultural practice to produce year-round diverse food items) and week multi-sectorial collaboration for nutritional intervention. Conclusion: In the study setting, diversified dietary habit of adolescents were affected by multiple layers of barriers. These multiple and interconnected influences were started from an individual level to multi-sectorial collaboration. To improve diversified dietary habit of adolescents’ nutritional intervention should be implemented at the individual, family, agricultural, and multi-sectorial levels.